Mathematics Applied to the Economy and Sustainable Development Goals: A Necessary Relationship of Dependence - Matilde Lafuente-Lechuga; Javier Cifuentes-Faura; Úrsula Faura-Martínez (MDPI AG, 2020)
Higher education must include training in sustainability to make all actors aware of the serious problems our planet is facing. Mathematics plays an important role in the achievement of the Sustainable Development Goals (SDG) and at the same time these allow working with real situations in the subject of mathematics, providing the student with active learning. Sustainability is used to make the student see the usefulness of mathematics while instilling values and attitudes towards it. A set of problems have been raised during the academic year that are solved with the developed mathematical techniques, and through a survey, the students' perceptions about the usefulness of mathematics to reach the goals established in the SDG has been evaluated. The results show that, regardless of the student's gender, the student's assessment of the usefulness of this subject in solving real problems improved. It has been observed that this teaching methodology has helped to motivate students and even those who do not like this subject have improved their appreciation of it.